How can Environmental Health Practitioners contribute to ensure population safety and health during the COVID-19 pandemic?. (April 2021) - Rodrigues, Matilde A.; Silva, Manuela V.; Errett, Nicole A.; Davis, Gayle; Lynch, Zena; Dhesi, Surindar; Hannelly, Toni; Mitchell, Graeme; Dyjack, David; Ross, Kirstin E.
Highlights: The role of Environmental Health Practitioners (EHPs) during pandemic is discussed. EHPs have played an essential and influential role in the response to COVID-19. EHPs roles in safety assessment, policy development and assurance were discussed. Limited human resources may increasing other public health and safety risk factors. Future policies should reflect value of local intervention. Abstract: The COVID-19 pandemic highlighted the relevance of public health professionals all over the world, in particular Environmental Health Practitioners (EHPs), who played a major role in the containment of the novel coronavirus, SARS-CoV-2. However, as in past disasters, their involvement was oriented towards urgent tasks, and did not fully utilize EHPs' competences and skills. Additionally, due to limited resources, during emergencies EHPs may temporarily transition away from their day-to-day role, potentially increasing other public health and safety risk factors without appropriate surveillance or intervention. To overcome this and prepare for possible future pandemics, it is important to identify and discuss the key roles of EHPs in different countries, providing a common framework for practices that can contribute to population safety and health. To this end, an international workgroup was established to discuss current environmental health practices and challenges across different countries during the pandemic. Findings from discussions concluded that, despite the observed differences across the countries, EHPs are one of the main public health emergency preparedness and response actors. However, since resources are still lagging significantly behind need, we argue that the role of these professionals during pandemics should be focused on practices that have higher impact to support population health and safety.